Hybrid reclining chair: design inspired from cuttlefish bone / Ridzuan Adli Azidin - Azidin, Ridzuan Adli (2013)
The study room is where the people doing their work. They spend most of the time after coming back from office especially for working adult. Furthermore, furniture in study room also plays a very important role in perform some activities like sleeping, relaxing or reclining. Furniture in study room not just for use only but it must have an aesthetic value. The research provides an attempt to redesign an existing normal shape of home chair into organic concept that have a aesthetic value and it can be use in a multi way of sitting posture. Out of several furniture in study room that can be listed, only one of furniture being focused through certain justification. Several of method being used such as observation, literature review, peer review and reference implemented in this study. Quantitative method was used to get the final concept of the product. The finding suggests that the home chair need to have a multi way of sitting posture and ergonomic to sit in multi way of position. Also the furniture must have an aesthetic value in terms of form and shape. Most of the existing home chair just have a simple shape and not more than just for one purpose. In a nutshell, the organic concept would be suitable to apply in designing hybrid chair in study room area with multi way of sitting posture.